DISEÑO DE UN SISTEMA DE GESTIÓN AMBIENTAL PARA LA INDUSTRIA MADERERA ORLY INTRIAGO S.A. - Tubay Bravo, Daniela Estefanía (2023)
At present, industrial development has generated environmental issues, which we are already familiar with. The management model of ISO 14001:2015 standard aims to maintain the current performance levels in the Orly Intriago timber industry, promoting necessary changes within the organization. The main objective of this project is to design an environmental management system in the Orly Intriago S.A. timber industry based on the international ISO 14001:2015 standard. It is expected to assess the current situation of the industry in order to identify the most significant impacts that directly or indirectly affect the environment, including nearby residents.